Ionic liquids as hydrotropes: the key towards solubility increase - Martins, Afonso Cerqueira (2022)
Water solubility of hydrophobic compounds is a crucial factor in the formulation of drugs, cleaning products and personal hygiene. Therefore, technology that allows us to increase their solubility and dissolution rate has attracted considerable interest not only at an academic level but also at an industrial one. In this sense, hydrotropes have been under the spotlight. These compounds are characterized as molecules possessing the capacity of promoting a drastic, several-fold increase in aqueous solubility of highly hydrophobic compounds. Recently, ionic liquids have been appointed as a promising class of catanionic hydrotropes, since both the cation and anion can contribute to the solubility increase. Although there is a vast amount of reviewing work centred on hydrotropy, its underlying mechanism is not yet fully understood. This work proposes to study the impact of salt addition on the hydrotropy phenomenon as to better understand its mechanism, both experimentally and through simulation. Herein the addition of chloride salts to aqueous solutions of an ionic liquid was found to hinder solubility by promoting aggregation of the latter, with a notably nuanced behaviour according to the salt cation valence. Hydrophobic interactions were found to be central to the aggregative effect of the hydrotrope around the solute, which seem to drive hydrotropy. The interactions between the hydrotrope and the solute presented a degree of site-specificity, lost with salt addition. Hydrotrope aggregation showed to be detrimental to the hydrotropic effect, disproving one of the dominant theories justifying the mechanism of hydrotropy.